The Marginality of the Gothic: A Reconsideration - Kliś, Agnieszka (Text Matters: A Journal of Literature, Theory and Culture, 2012)
It is commonly accepted that we discuss the Gothic in terms of the margin. These two seem to be inseparable and associating them appears “just natural.” However, in light of the contemporary critical debate on the ubiquity of the Gothic, the mode’s “natural” marginality might appear somewhat out of place. While the Gothic is still increasingly popular in popular culture, it has also become incredibly popular among literary scholars. In fact, it not only permeates the culture we live in, but it also appears to occupy a mainstream position in academia these days. Viewing the Gothic as a notion shaped to a certain extent by the critic, this article investigates—and reconsiders—the persistence of the Gothic margin in contemporary critical discourse. Following Paul A. Bové’s consideration of the ways in which institutionalized criticism partakes in discourse, it sees contemporary Gothic criticism as at least potentially operating within discourse in Michel Foucault’s terms, and thus considers the possibility of the Gothic margin being in fact a critical construct, functional within the contemporary discourse of criticism. Hence, the article poses questions about the origin of Gothic marginality, the contemporary status of the Gothic margin and its potential functionality, and finally, possible results of the loss of the marginal status for the Gothic as a critical object. It seeks the answers by means of scrutinizing critical accounts, such as Fred Botting and Dale Townshend’s introduction to the Critical Concepts series on the Gothic, and by contrasting different attempts at (re)presenting the Gothic and its status. Finally, it considers the distinction between the past—the era of critical neglect—and the present—allegedly the times of the vindication of the Gothic. In so doing, it aims at determining whether and why the marginality of the Gothic could indeed turn out to be constructed by the critics.